Regional Transformation in Russia - Horváth, Gyula (Discussion Papers, 2012)
After several years of debate and inconclusive results, the problems of regional policy have now come to the fore of the political agenda in the Russian Federation. The 1993 Constitution left the issue of state structure far from resolved. There has been no effective institution for implementing regional policy. The central leader¬ship has declared a clear commitment to federalism. In the current situation, how¬ever, ill-conceived attempts in the area of regional development might result in a backtrack to unitarism and a compromise of democratic values in an effort to strengthen central state control. Russia inherited from the Soviet Union an economic structure that was geo¬graphically highly unbalanced. Capital accumulation and industrial location were a result of a concerned government policy to locate key industry in a small number of regions. But even after the collapse of the Empire, the gap between more pros¬perous regions, including Moscow and St. Petersburg, and less developed ones, has not been reduced. Actually, the gap has widened during the last decade of transi¬tion. The paper describes regional disparities and their influencing factors, analyses regional socio-economic imbalances, losers and winners of the transition. Finally, it gives a summary of regional development policy documents and main targets of the regional policy.